A Study of Tea Pluckers’ Perception on the Introduction of Tea Plucking Machines in James Finlay’s Kenya (International Journal of Scientific Research and Management (IJSRM), 2018)
This study sought to assess the perception of tea pluckers on the introduction of tea plucking machines in James Finlay’s Kenya. The research was a case study of one of the major tea industry players; James Finlay’s Kenya Ltd. The target populations were all the tea estates in James Finlay’s (K) Ltd in Kericho County. James Finlay’s has a total of 13 Tea estates. There are a total of 10,262 tea pluckers in the company. A sample of five estates was considered and a sample of 20% of tea pluckers in these estates was taken for the study. A representative group according to Mugenda and Mugenda is one that is at least 10% of the population of interest. The above sample was therefore representative. Data was collected using structured questionnaires and interview methods. The data collected was supplemented with available literature review on the subject of study. The response from cross-functional sample group was analysed using descriptive statistical techniques in form of frequency distribution tables, percentages, pie charts, and computer packages. The study found that the tea pluckers viewed the introduction of the machines negatively; they interpreted it as a way of rendering them obsolete and eventually retrenching them. They therefore did not fully support its implementation